Itsbat Marriage of Sirri Polygamy in Progressive Law Perspective, Case Study of Decision Number 5065/Pdt.G/2019/PA.Clp - Ummu Salamah Nur Rohmawati (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
A case concerning an application for itsbat marriage at the Cilacap Religious Court filed by a husband and his second wife. Their marriage was conducted siri without the knowledge of the first wife. This application was filed to obtain legalisation of their siri marriage so that it could be officially recorded, which has implications for the legality of children born from the marriage and other civil rights. The purpose of this research is to find out the considerations and factors behind a Judge granting a marriage isbat application. then the second objective is to analyse the results of Decision Number 5065/Pdt.G/2019/PA.Clp in terms of progressive law. This type of research is library research using a normative juridical approach using progressive legal theory. The conclusion in Itsbat Marriage Case in Decision Number 5065/Pdt.G/2019/PA.Clp is that the judge considers aspects of humanity, social justice, and benefits for all parties involved. From the aspect of substantive justice, the decision reflects an approach that takes into account the best interests of the child, harmony in the family, and the protection of women's rights. In the context of the judge's background, the granting of this decision may have been influenced by a deep understanding of the social and cultural values of the local community, as well as a broad understanding of religious norms relating to marriage. The judge may also have considered the urgency of protecting children's rights and the need to resolve family conflicts fairly and peacefully. As such, the granting of this decision demonstrates the judge's commitment to achieving substantive justice in accordance with the social, cultural and religious values of the community, while ensuring the protection of the rights of the individuals involved in the case.